2012
DOI: 10.1080/19475705.2011.604799
|View full text |Cite
|
Sign up to set email alerts
|

Model of electric discharge formation in the lower atmosphere over a seismic region

Abstract: The altitude distribution of seismic-related direct current (DC) electric field in the Earth-ionosphere layer is computed. This field is generated by the conductivity current flowing in closed atmosphere-ionosphere electric circuit at the preparatory stage of an earthquake. The source of the current is electromotive force caused by upward convective transport and gravitational sedimentation of charged aerosols injected into the atmosphere by soil gases in the course of intensification of seismic processes. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Sorokin et al (2001Sorokin et al ( , 2005aSorokin et al ( , 2006aSorokin et al ( , 2007 and Sorokin and Chmyrev (2010) carried out the theoretical investigation of mechanisms of EMF formation in the lower atmosphere, who have shown that the quasi-static electric field reaches 10 mV/m in the ionosphere while their value is of the order of 100 V/m on the Earth's surface. Moreover, the field can reach a breakdown value in the layer with thin 1-2 km on the altitudes 5-10 km in the troposphere (Sorokin et al, 2011(Sorokin et al, , 2012a. Value of the external current of EMF can be approximately 10 -8~1 0 -6 A/m 2 near the ground.…”
Section: Lai Comentioning
confidence: 99%
See 1 more Smart Citation
“…Sorokin et al (2001Sorokin et al ( , 2005aSorokin et al ( , 2006aSorokin et al ( , 2007 and Sorokin and Chmyrev (2010) carried out the theoretical investigation of mechanisms of EMF formation in the lower atmosphere, who have shown that the quasi-static electric field reaches 10 mV/m in the ionosphere while their value is of the order of 100 V/m on the Earth's surface. Moreover, the field can reach a breakdown value in the layer with thin 1-2 km on the altitudes 5-10 km in the troposphere (Sorokin et al, 2011(Sorokin et al, , 2012a. Value of the external current of EMF can be approximately 10 -8~1 0 -6 A/m 2 near the ground.…”
Section: Lai Comentioning
confidence: 99%
“…Moreover, the appearance of irregularities in the nighttime ionosphere leads to depressions of ULF pulsations of magnetosphere origin (Sorokin et al, 2004;Schekotov et al, 2006;Hayakawa et al, 2013). The growth of electric field up to the breakdown value is caused by random electric discharges, which might generate VHF radio emission in the troposphere over the EQ epicenter (Sorokin et al, 2011(Sorokin et al, , 2012a. The generation of conductivity current in the global circuit is accompanied by the modification of ionosphere.…”
Section: Lai Comentioning
confidence: 99%